Inositol polyphosphate multikinase is a metformin target that regulates cell migration - Tu-Sekine, Becky (FASEB J, 2019)
Metformin has been shown to alter cell adhesion protein expression, which is thought to play a role in its observed antitumor properties. We found that metformin treatment down-regulated integrin β1 concomitant with the loss of inositol polyphosphate multikinase (IPMK) in murine myocytes, adipocytes, and hepatocytes. To determine if IPMK was upstream of integrin β1 expression, we examined IPMK(−/−) mouse embryonic fibroblast cells and found that integrins β1 and β3 gene expression was reduced by half, relative to wild-type cells, whereas focal adhesion kinase (FAK) activity and Rho/Rac/Cdc42 protein levels were increased, resulting in migration defects. Using nanonet force microscopy, we determined that cell:extracellular matrix adhesion and cell contractility forces were decreased, confirming the functional relevance of integrin and Rho protein dysregulation. Pharmacological studies showed that inhibition of both FAK1 and proline-rich tyrosine kinase 2 partially restored integrin β1 expression, suggesting negative regulation of integrin β1 by FAK. Together our data indicate that IPMK participates in the regulation of cell migration and provides a potential link between metformin and wound healing impairment.—Tu-Sekine, B., Padhi, A., Jin, S., Kalyan, S., Singh, K., Apperson, M., Kapania, R., Hur, S. C., Nain, A., Kim, S. F. Inositol polyphosphate multikinase is a metformin target that regulates cell migration.